The source of business profits (Ellis, 1887)
Repr. from the Quarterly Journal of Economics, April 1887. Facsimile reprint: New York, Arno Press & The New York Times, 1970. (American labor. From conspiracy to collective bargaining. Advisory editors: L. Stein en Ph. Taft). In: Wages, hours, and strikes: ...